1961
DOI: 10.1103/physrev.124.246
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Model of Elementary Particles Based on an Analogy with Superconductivity. II

Abstract: Continuing the program developed in a previous paper, a "superconductive" solution describing the proton-neutron doublet is obtained from a nonlinear spinor field Lagrangian. We Gnd the pions of Gnite mass as nucleon-antinucleon bound states by introducing a small bare mass into the Lagrangian which otherwise possesses a certain type of the p5 invariance. In addition, heavier mesons and two-nucleon bound states are obtained in the same approximation. On the basis of numerical mass relations, it is suggested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
2,383
2
17

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,769 publications
(2,450 citation statements)
references
References 31 publications
26
2,383
2
17
Order By: Relevance
“…Furthermore, several types of mechanism may lead to the occurrence of massless pseudoscalar bound states, in connection with the spontaneous breakdown of chiral symmetry. Two such mechanisms are : i) the dynamical fermion mass generation, due to radiative corrections in the fermion self-energy part [21];…”
Section: Zero Mass Solutionsmentioning
confidence: 99%
“…Furthermore, several types of mechanism may lead to the occurrence of massless pseudoscalar bound states, in connection with the spontaneous breakdown of chiral symmetry. Two such mechanisms are : i) the dynamical fermion mass generation, due to radiative corrections in the fermion self-energy part [21];…”
Section: Zero Mass Solutionsmentioning
confidence: 99%
“…The NJL model was originally developed to describe interactions between structureless nucleons [24]. It has been shown that this approach does not lead to nuclear stability [25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The singularity of θ j can be transferred to a singularity of the gauge field by a gauge transformation. We consider the case θ 2 = −θ 1 : φ = 2θ 1 …”
Section: Non-trivial Configuration Of Gauge Fieldsmentioning
confidence: 99%